A HYPERTENSIVE RESPONSE TO EXERCISE IS ASSOCIATED WITH AN ALTERATED CARDIOVASCULAR RISK PROFILE: A SYSTEMATIC REVIEW AND META-ANALYSIS. (April 2021) - Moore, Myles; Climie, Rachel; Otahal, Petr; Sharman, James; Schultz, Martin
Abstract: Objective: A hypertensive response to exercise (HRE) is a risk factor for cardiovascular disease and reveals high blood pressure (BP) not detected at rest. Alterations to markers of cardiovascular risk may underlie associations between HRE and high BP, although this has not been systematically elucidated. This study aimed to assess relationships between HRE and cardiovascular risk markers via systematic review and meta-analysis of published literature. Design and method: Three online databases were searched from inception to July 2019 for studies reporting associations between exercise BP and cardiovascular risk markers (including lipid, metabolic, inflammatory and vascular stiffness markers). Pooled mean differences (random effects) were calculated for each cardiovascular risk marker between individuals with and without HRE. Univariable meta-regressions were performed to assess differences in pooled mean differences by resting hypertension and health status, intensity at the time BP was measured and exercise modality. Results: Overall, 37 studies with 37, 878 participants (aged 50 ± 3years; 79% male) were included. On average, individuals with HRE had elevated total cholesterol (26 studies, pooled mean difference 0.13 ± 0.08mmol/L, p < 0.001), low-density lipoprotein cholesterol (17 studies, 0.12 ± 0.03mmol/L, p < 0.001), triglycerides (22 studies, 0.24 ± 0.04mmol/L, p < 0.001), glucose (21 studies, 0.15 ± 0.05mmol/L, p = 0.002), white blood cell count (4 studies, 0.49 ± 0.16x109 cells, p = 0.003), and aortic pulse wave velocity (3 studies, 0.8 ± 0.35m/s, p = 0.02), compared to those without HRE. Participants with HRE also had decreased high-density lipoprotein cholesterol (20 studies, -0.03 ± 0.01mmol/L, p = 0.003) and impaired flow-mediated dilation (2 studies, -4.13 ± 1.02%, p < 0.0001) compared to those without HRE. All pooled mean differences between HRE and no HRE were similar irrespective of resting hypertension and health status, exercise intensity and modality, except low-density lipoprotein cholesterol which had a greater mean difference during treadmill testing compared to cycling (p = 0.036), and aortic pulse wave velocity, which had a smaller mean difference in athletes compared to general populations (p = 0.018). Conclusions: HRE is associated with alterations in cardiovascular risk markers including increased lipid, metabolic, inflammatory and vascular stiffness and function markers. Associations varied with health status and test modality, but were consistent irrespective of resting hypertension status and exercise intensity. Results further highlight the advanced cardiovascular risk associated with HRE.